LANGUAGE VARIATION: REGISTER AND ACCENT IN KEN AROK AND KEN DEDES DRAMA PERFORMANCE - Syafri, Frimadhona (Universitas Negeri Semarang, 2013)
Language and culture are inseparable. When people communicate to one another, they take their culture in communication; they may use the same language, but differences in accent show their register.Ã‚Â Language variation covers distinctions in pronunciation, grammar, or word choice within a language. It includes register and accent. This concept is reflected in the performance of Ken Arok and Ken Dedes. In the performance, the register described a group of people and their roles in the community.Ã‚Â It is interesting to analyze English with Javanese accents and register in the drama performance. In this performance, speaking English with Ã‚Â Javanese accent does not reduce the traditional values of Javanese culture.